Pengaruh Kompensasi Finansial dan Kompensasi Non Finansial Terhadap Kinerja Karyawan - Fadhilah, Irfan; Sri Ramadhani; Muhammad Ikhsan Harahap (Forum Kerjasama Pendidikan Tinggi, 2025)
This study aims to determine the effect of financial and non-financial compensation on employee performance, the study was conducted at PT Wahana Trans Lestari Medan Jalan Jendral Gatot Subroto Number 148 Medan Petisah. The research method used quantitative research methods, the technique of collecting data through observation, interviews, and questionnaires. The data processing application uses the SPSS version 24.00. The results of the study are 1. Financial Compensation has a positive effect on Employee Performance, this is indicated by positive results, namely the Financial Compensation Variable shows a calculated t value greater than the t table (5.921> 1.842), or sig <? (0.001 <0.005). 2. Non-Financial Compensation has a positive effect on Employee Performance, this is indicated by positive results. It can be seen that the Non-Financial Compensation Variable shows a calculated t value greater than the t table (3.871> 1.842), or sig <? (0.000 <0.005). 3. Based on the F test, the calculated F value is 356.093, this value is greater than 2.70 or Fcount 354.093> Ftable 2.70 with a probability of 0.000. Because the probability value is much smaller than 0.05, it can be said that the Financial Compensation Variable and Non-Financial Compensation together or simultaneously have a positive effect on Employee Performance at the PT. The conclusion is that the third hypothesis is accepted.